Namibia : Staff Report for the 2005 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
This 2005 Article IV Consultation highlights that Namibia recorded robust real GDP growth, falling inflation, a strong external current account surplus, and continued low external indebtedness over the last two years. Real GDP grew by 6 percent in 2004, as new marine technologies prompted a surge in diamond production and most other sectors of the economy showed solid economic activity, aided by a decline in interest rates. Growth slowed in 2005, as diamond production fell relative to the high production base of the previous year and growth rates in other sectors moderated somewhat.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet